Comparison of Ultrasonic and QuEChERS Extraction Methods Efficiency for the Determination of Herbicides Residues in Soil and Maize Cob - Zondo, Sandisiwe; Mahlambi, Precious (Trends in Sciences, 2022)
In this study, the optimization and application of ultrasonic extraction and QuEChERS methods was conducted for the effective extraction of pesticides from maize and their corresponding soil samples. The characterization pesticides (Atrazine, glyphosate, 2,4-dichlorophenoxyacetic acid and mesotrione) was done with gas chromatography-flame ionization detector. Factors influencing the efficiency of the extraction methods such as the extraction solvent, extraction time, solvent volume and spiking concentration were assessed. Under the optimum experimental conditions, the recoveries of analytes ranged between 100 - 104 % in maize cop and 91 - 97 % in soil for ultrasonic method, while they were 94 - 115 % in maize cob and 89 - 101 % in soil for QuEChERS method. The repeatability, articulated as RSD values were less than 5 % for all analytes in both methods. The limits of detection and limit of quantification ranged from 0.02 - 0.15 µg L−1 and 0.2 - 0.5 µg L−1 for ultrasonic method and 0.01 - 0.23 µg L−1 and 0.13 - 0.8 µg L−1 for QuEChERS method. The lower limits of detection and quantification with higher recoveries suggests that both methods can be accurately applied for the determination of the assessed pesticides in soil and maize cop. Herbicides concentrations ranged between 0.33 - 45.10 µg L−1 in soil and 6.15 - 34.2 µg L−1 in maize cob. In all studied herbicides, maize residues detected were found to be higher compared to maize allowable maximum residue limits however, atrazine in all soil samples was found to be lower compared to soil allowable maximum residue limits. This indicates the importance of continuous monitoring the herbicides residues in maize to safeguard health for the consumers. HIGHLIGHTS Crops compete with lots of undesired plants that naturally grow and compete for carbon dioxide, space, nutrients, sunshine and water Agricultural sector plays a significant role in food security, production and steady supply by employing herbicides and agrochemicals to achieve high crop yield in a short space of time Crop and soil health are evaluated for herbicides toxicity as herbicides contains toxic chemicals that poses a risk to the consumer and the environment GRAPHICAL ABSTRACT